1927 Ind. Acts 469, § 2 - (:unkn) unknown (My University, 1927)
Operation of Machine Guns, Discharge of Bombs - Offense and Penalty:, ch. 156, § 2: Prohibited discharging a machine gun or bomb. Punishable by imprisonment for 2-10 years.
Keywords: DISCHARGE; MACHINE GUN RESTRICTION